Junctional adhesion molecule-C: A multifunctional mediator of cell adhesion - Ebnet, Klaus; Aurrand-Lions, Michel (Cellular and molecular life sciences : CMLS, 2025)
Junctional Adhesion Molecule-C (JAM-C) is a member of the JAM family of cell adhesion molecules. JAM-C is expressed by a large variety of tissues including epithelial and endothelial tissues, neuronal tissues, glial cells, cells of the reproductive system, or cells of the hematopoietic system. Through trans-homophilic as well as trans-heterophilic interactions with the JAM family member JAM-B and with members of the integrin family JAM-C regulates diverse processes including epithelial barrier formation, leukocyte– endothelial interactions and transendothelial migration, neuronal cell migration along glial fibers, myelin sheath integrity, and germ cell migration. In this article, we review the biological activities of JAM-C, including its basic organization, its extracellular and intracellular interaction partners, and its diverse physiological functions.